Diffusion tensor imaging reveals no white matter impairments among adults with autism spectrum disorder. Issue 1 (30th July 2015) - Kirkovski, Melissa; Enticott, Peter G.; Maller, Jerome J.; Rossell, Susan L.; Fitzgerald, Paul B.
Abstract: Abnormalities within white matter (WM) have been identified in autism spectrum disorder (ASD). Although there is some support for greater neurobiological deficits among females with ASD, there is little research investigating sex differences in WM in ASD. We used diffusion tensor imaging (DTI) to investigate WM aberration in 25 adults with high-functioning ASD and 24 age-, sex- and IQ-matched controls. Tract-based spatial statistics (TBSS) was used to explore differences in WM in major tract bundles. The effects of biological sex were also investigated. TBSS revealed no differences in fractional anisotropy (FA), mean diffusivity (MD), radial diffusivity (RD), or axial diffusivity (AD) between groups. There were no effects of biological sex. We consider whether methodological differences between past studies have contributed to the highly heterogeneous findings in the literature. Finally, we suggest that, among a high-functioning sample of adults with ASD, differences in WM microstructure may not be related to clinical impairment. Highlights: Whole brain DTI reveals no white matter impairment in adults with ASD. No effects of biological sex on white matter integrity in ASD. WM integrity was not related to symptomatology in high functioning adults with ASD.